Brucite – Industrial Mineral with a Future - Simandl, George; Paradis, Suzanne; Irvine, Melanie (Geoscience Canada, 2007)
Brucite, Mg(OH)2, is an uncommon mineral primarily known to mineral collectors, and to specialists studying contact metamorphic and ultramafic rocks. It is an environmentally friendly flame-retardant and is in commercial demand; it also represents a potential ore source for the metal, magnesium, which is itself in great demand. The present brucite market for flame-retardants is less than 50 000 tonnes annually, but it is increasing exponentially. Brucite has the advantage of not containing CO2; hence none is released during calcination, a positive feature in today’s society concerned with climate change. This review paper summarises the topic for scientists studying the thermodynamic properties of brucite, geologists studying its contact meta-morphic characteristics, exploration geologists and potential end-users. Given the demand for the mineral and metal, high-grade brucite deposits may become hot exploration targets within the next few years.